Pengaruh Media Big Book Terhadap Keterampilan Literasi Pada Pembelajaran Bahasa Indonesia Siswa Kelas II SD - Kotimah, Khusnul; Wibowo, Satrio; Maqfiro, Mochammad Ludfy Hadis (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The dearth of student understanding at some stage in learning of literacy abilties, in particular analyzing and writing. This makes researchers very confident in discovering this hassle with the assist of big e-book media. This observe makes use of a quantitative experiment with a Nonequivalent manipulate group design which objectives to determine whether or not or now not there may be an impact of huge book media on literacy capabilities in grade II Indonesian language studying. information series was taken the usage of pretest, posttest, and questionnaire questions, in addition to easy linear regression evaluation performed to set the hypothesis. based at the results acquired, literacy capabilities assisted by way of huge e book media within the experimental elegance got a posttest rating of 89.33%, and within the manage magnificence without the assist of big book media got a posttest rating of 59.33%. The t take a look at inference effects show that the t test is three.356> t table 2.100 and zero.00 <0.05 means H0 is rejected. With the outcomes of the purchase of scholar response questionnaires got 81%. based on the effects on this take a look at, it is able to be concluded that there's an effect of the use of large e-book media on literacy abilities in grade II Indonesian language mastering and there's a response to gaining knowledge of the use of massive book media on literacy abilities in grade II Indonesian language mastering.